An Evaluation of Survival English Textbook Used in Teaching Speaking for First Semester Students in English Education Study Program - Felicia Lekatompessy (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
Textbooks are one of the important components in language program. It plays significant roles to provide the basis for content of the lesson, the balance of skills taught and the kinds of language practice that students involve in (Richards, 2001). Due to this circumstance, the use of qualified and relevant textbook is highly required to facilitate learning and bring actual learning experience to students. In addition to the selection, the evaluation of the textbooks in EFL context are also at the utmost importance to evaluate whether a particular textbook used in the classroom is a good textbook or not. This study was aimed to evaluate the suitability of the Survival English textbook based on the Content and Contexts criteria of a good English textbook, which proposed by Mukundan (2011), Mukundan et al (2012) and Miekley (2015). The list of statements in a form of questionnaire were addressed to identify 50 students’ assessment of six topics being discussed in the textbook, which was supported by the qualitative data from the interview session. The results of the study were found substantial as the input to develop further Survival English textbook